DEVELOPMENT OF DIGITAL PICTORIAL STORY BOOK BASED ON MULTIPLE INTELLIGENCES FOR GRADE V STUDENTS OF SDS YASPORBI III JAKARTA - Febrianti Yuli Satriyani; Suci Lihuna Yanto (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2020)
This study aims to produce a digital pictorial story book based on multiple intelligences that are theoretically valid and effective to improve the narrative writing skills of grade V SDS Yasporbi III students. The research was conducted using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The results of the product validation value developed by media experts were 83.8%, material experts were 84.2%, linguists were 82.2%, and practicing experts were 97.7%. From the resulting average score, the product can be categorized as very valid or very feasible to use. The level of product attractiveness is based on the field trial stage for students obtained a value of 91% which is categorized as very attractive. The use of digital picture books based on multiple intelligences on theme 5 “Love Indonesia” has proven to fulfill the feasibility aspect for use in learning and has succeeded in improving students' narrative writing skills and facilitating the multiple intelligences of grade V SDS Yasporbi III students. This can be proven from the results of the students' post-test scores during field trials. The results of student scores have increased by 21.12%, namely from the average percentage of pre-test scores before using the product of 70.2% where only 4 out of 18 students passed the minimum completeness standards and the average percentage of student scores during the post -test or after using the product of 89% where all students passed the minimum completeness standard.